1998
DOI: 10.1128/jvi.72.6.4746-4755.1998
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and Functional Analysis of the C-Terminal Region of the C3H Mouse Mammary Tumor Virus Superantigen

Abstract: The mouse mammary tumor virus (MMTV) encodes within the U3 region of the long terminal repeat (LTR) a protein known as the superantigen (Sag). Sag is needed for the efficient transmission of milk-borne virus from the gut to target tissue in the mammary gland. MMTV-infected B cells in the gut express Sag as a type II transmembrane protein that is recognized by the variable region of particular beta chains (Vβ) of the T-cell receptor (TCR) on the surface of T cells. Recognition of Sag by particular TCRs results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Clumps were removed on ice by settling for 5 min, and single cells were washed several times in FACS buffer before staining. Peripheral blood lymphocytes were obtained and purified as described previously (53,54). Cells (approximately 10 6 ) were incubated with antibody specific for V␤3, -5, -6, -7, -8, -9, -11, -12, or -14 labeled with fluorescein and CD4-or CD8-specific antibody labeled with phycoerythrin (PharMingen, San Diego, Calif.).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clumps were removed on ice by settling for 5 min, and single cells were washed several times in FACS buffer before staining. Peripheral blood lymphocytes were obtained and purified as described previously (53,54). Cells (approximately 10 6 ) were incubated with antibody specific for V␤3, -5, -6, -7, -8, -9, -11, -12, or -14 labeled with fluorescein and CD4-or CD8-specific antibody labeled with phycoerythrin (PharMingen, San Diego, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…The mouse mammary tumor virus (MMTV) superantigen (Sag) protein is necessary for the efficient transmission of virus from infected mother's milk to the mammary glands of offspring (23,54). MMTV transmission requires infection of both B and T lymphocytes to facilitate transport of virus from the gut of newborns to mammary cells, and lymphocytes appear to be a reservoir of virus in the postnatal period prior to mammary gland development (7,23,26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results using splice donor site mutants of MMTV and TBLV in BALB/c mice indicated that MMTV-encoded Rem is involved in antagonizing proviral mutagenesis by Apobec family enzymes, including AID (18). Although Sag-mediated amplification of infected B and T lymphocytes is needed for efficient MMTV transmission and mammary cancer development (27, 30, 42), TBLV does not require Sag for the induction of T-cell lymphomas (38). Therefore, using Sag-independent TBLV, we tested the effect of Rem loss in multiple strains of genetically engineered mice that are available on the B6 background.…”
Section: Resultsmentioning
confidence: 99%